At Intersections of Technology and a Modern Mass Medium: The Engineer Robert Runeberg and Exhibitions, 1867–1900. Issue 1 (1st January 2017) - Syrjämaa, Taina
Abstract : This article examines the intersections of technology and the exhibition medium by focusing on an individual, the mechanical engineer Robert Runeberg. It makes visible individual involvement in transnational mobility and in large-scale processes of modernization. The article explores how becoming a modern professional was not only connected to formal education and practical training, but also to the capacity to extract and produce knowledge via the exhibition medium. Concurrently, the case discloses essential qualities, such as the cohesion, dynamicity and flexibility of the exhibition medium.